Evaluating Best Methods for Crisis Resource Management Education: Didactic Teaching or Noncontextual Active Learning. Issue 6 (December 2019) - Saravana-Bawan, Bianka B.; Fulton, Courtney; Riley, Brigitta; Katulka, Jeremy; King, Sharla; Paton-Gay, Damian; Widder, Sandy
Abstract : Introduction: Health care training traditionally focuses on medical knowledge; however, this is not the only component of successful patient management. Nontechnical skills, such as crisis resource management (CRM), have significant impact on patient care. This study examines whether there is a difference in CRM skills taught by traditional lecture in comparison with low-fidelity simulation consisting of noncontextual learning through team problem-solving activities. Methods: Two groups of multidisciplinary preclinical students were taught CRM through lecture or noncontextual active learning. Both groups were given a cardiopulmonary resuscitation simulation and clinical performance assessed by basic life support (BLS) checklist and CRM skills by Ottawa Global Rating Scale. The groups were reassessed at 4 months. A third group, who received no CRM education, served as a control group. Results: The mean BLS scores after CRM education were 18.9 and 24.9 with mean Ottawa Global Rating Scale (GRS) scores of 22.4 and 29.1 in the didactic teaching and noncontextual groups, respectively. The difference between intervention groups was significant for BLS ( P = 0.02) and Ottawa GRS ( P = 0.03) score. At 4-month follow-up, there was no statistically significant difference in BLS ( P = 1.0) or Ottawa GRS score ( P = 0.55) between intervention groups. In comparison with the control group, there was a marginally significant difference in Ottawa GRS score ( P = 0.06) at 4-month follow-up. Conclusions: Noncontextual active learning of CRM using low-fidelity simulation results in improved CRM performance in comparison with didactic teaching. The benefits of CRM education do not seem to be sustained after one education session, suggesting the need for continued education and practice of skills to improve retention.